2022
DOI: 10.1371/journal.pone.0265140
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of AstraZeneca COVID-19 vaccine side effects among Nigist Eleni Mohammed memorial comprehensive specialized hospital health workers. Cross sectional survey

Abstract: Introduction The best way to eradicate corona virus disease (COVID-19) viral infection is mass vaccination. Many studies demonstrate vaccination is associated with some local and systemic side effects. This study aimed to provide evidence on AstraZeneca COVID-19 vaccine side effects. Methodology Institutional based cross-sectional survey was conducted among 254 health workers at Nigist Eleni Mohammed memorial comprehensive specialized hospital (from July 01/ 2021 to July 30/2021). Data were collected consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 15 publications
7
22
1
Order By: Relevance
“…Since there is an eight- to 12-week interval between administering the Oxford–AstraZeneca (AZD 1222) doses [43] , most researchers have evaluated the SEs of only the first dose [35] , [44] , [45] , [46] , [47] , [48] , [49] rather than the SEs of both doses [39] , [50] . Our study reported that Oxford–AstraZeneca was associated with the highest prevalence of SEs following the first dose (93.8 %).…”
Section: Discussionmentioning
confidence: 99%
“…Since there is an eight- to 12-week interval between administering the Oxford–AstraZeneca (AZD 1222) doses [43] , most researchers have evaluated the SEs of only the first dose [35] , [44] , [45] , [46] , [47] , [48] , [49] rather than the SEs of both doses [39] , [50] . Our study reported that Oxford–AstraZeneca was associated with the highest prevalence of SEs following the first dose (93.8 %).…”
Section: Discussionmentioning
confidence: 99%
“…The same study revealed that more side-effects were significantly associated with the Oxford/AstraZeneca vaccine than other vaccines. Additionally, a study conducted among health workers in Ethiopia reported a 91.3% prevalence of AstraZeneca COVID-19 vaccine side-effects [ 12 ]. The differences could be explained by differences in populations, as some of them could present differing thresholds for discomfort, as well as the nocebo effect in that, some populations could be more averse to rumors and misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that 78.8% of our study participants received the AstraZeneca vaccine and it is a fair comparison to this Ethiopian study whose participants also received the AstraZeneca vaccine. Another Ethiopian study among healthcare workers vaccinated against COVID‐19 by Desalegn et al 41 . had a COVID‐19 vaccine side‐effect prevalence of 91.3% among respondents after the first dose and that of the second dose was 67%.…”
Section: Discussionmentioning
confidence: 97%
“…Another Ethiopian study among healthcare workers vaccinated against COVID‐19 by Desalegn et al. 41 had a COVID‐19 vaccine side‐effect prevalence of 91.3% among respondents after the first dose and that of the second dose was 67%. With regard to our study, there was a slight reduction in prevalence of adverse event as we recorded 87.9% after the first dose but a higher prevalence of 75.6% after the second dose as compared to the Ethiopian study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation